(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Disorder of sexual development (DSD) is defined as a diverse group of congenital conditions in which the development of chromosomal, gonadal and anatomic sex is different or incongruent. It has replaced older terminology like intersex, pseudo hermaphroditism or ambiguous genitalia. These conditions, affecting approximately 1 in 4500 newborns, arise from variations in the complex genetic and hormonal pathways that govern sexual development. The exact data on the incidence or prevalence of DSD in Bangladesh is limited. Bangladesh Medical University (BMU) is the largest tertiary care hospital in Bangladesh, which is considered as the ultimate referral center for such complex cases as DSD. The DSD cases that are commonly encountered in the department of Endocrinology, BMU, include congenital adrenal hyperplasia (CAH), complete androgen insensitivity syndrome (CAIS), gonadal dysgenesis, Leydig cell hypoplasia, etc. However, there are no adequately designed studies to observe the frequency or pattern of DSD at our institute. In this scientific paper, we try to enumerate the approach to a patient with DSD presented at our institute and the common barriers that we encounter. We envision an internationally concerted collaboration among the endocrinologists and biochemists/pathologists involved in this field of patient management at home and abroad in the upcoming days. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S17]